Congestion and Residential Moving Behaviour - Morten Marott Larsen; Ninette Pilegaard; Jos van Ommeren (Tinbergen Institute, 2004)
In this paper we study how congestion and residential movingbehaviour are interrelated using a two-region job search model. Workerschoose optimally between interregional commuting and residential movingto live closer to the place of work. This choice affects the external costs ofcommuting due to congestion. The welfare maximizing road tax is derived.We demonstrate that road pricing may not only reduce congestion but alsoincrease total residential moving costs in the economy. One of the mainconsequences is that the road tax does not necessarily increase welfare.
Keywords: R23; R41; 330; Congestion; Residential Moving and Job Search; Bottleneck; Wohnungswechsel; Suchtheorie; Theorie